Fabrication of artificial defects using 3D printing for Non-Destructive Testing (NDT) applications - Yeo, Zong Han (Nanyang Technological University, 2020)
Three specimens with sub-surface defects were designed and printed using an additive manufacturing process called selective laser melting. The three defects were strictly based on the specimen defects 5, 7 and 8 of the NDE Sonaspection Education kit. The purpose was to evaluate the viability of 3D printing the NDE Education kit. Tests such as the ‘A’ scan and ‘C’ scan were used to analyse the printed subsurface defects. ‘A’ scan and ‘C’ scan were successful in locating the printed defects at the correct length and depth. Given that the 6db drop technique was not as effective in measuring the defect's width, a new method was thus developed. The new method provided higher accuracy, with results deviating from only -7.08% to +66.5%. As such, compared to the other width sizing methods, the new method is highly suitable for assessing the defect’s width. A destructive test was used because there are no X-Ray machines available in the labs of Nanyang Technological University. Specimens were milled or wire-cut at a strategic position to protect its testability. Microscopic Testing was chosen to assess the accuracy of the additive manufacturing method. Acoustic attenuation and longitudinal material velocity measured on all three specimens were inconsistent, therefore the average of three specimens’ readings was used as a guidance to characterise the printed material. Additionally, the angle probe test was proven to not be effective due to the coarse grains of the 316L stainless steel material. This suggested that 316L stainless steel could not be a good material to replicate the NDE Educational kit.